Heat transfer properties of porous materials and insulants - Batty, William J. (Cranfield University, 1984)
Buildings are complex thermally-dynamic structures serving aesthetic as well as, utilitarian functions. It is essential that careful planning is undertaken if buildings are to be energy efficient and cheap to run throughout their-expected life-spans. Although regulations have recently been introduced requiring the values of thermal transmittances (i. e. U-values) for walls and roofs of industrial and domestic buildings, to be less than specified limits, there is no guarantee that improved design will result. Also condensation has increasingly become a problem, as natural ventilation has been reduced, because of the introduction of doubleglazing and draught proofing. The use of insulating materials to increase thermal efficiencies " through the reduction of heat losses may also create problems in industrial plant and pipework. Metal structures covered with insulants are thereby hidden from view and so any ensuing corrosion, such as the general attack upon a low-alloy steel or stress-corrosion cracking of a stainless steel, may remain undetected until catastrophic failure occurs. It is, therefore, of utmost importance that the potential for and enhancement of corrosion due to the addition of insulants should be carefully considered. The ingress of water or water vapour into the insulant layer and subsequent leaching is the major cause of corrosion, and it is essential that steps are taken to prevent or reduce the likelihood of this occurring while ensuring that metal surfaces are adequately protected. There is a need to ascertain the heat and mass-transfer behaviours of building and insulating materials. Mathematical models require realistic data to simulate effectively conditions found in real structures. Too often in the past manufacturers' data for thermal properties, measured under laboratory conditions, have been used with little attempt to check on their validity or appropriateness to the conditions which are likely to be experienced. As desk-top computers become cheaper and more powerful these dangers could well increase. The too prevalent trusting attitude that computer predictions are absolutely correct together with a potential lack of understanding of the concepts of heat transfer and moisture mitigation by the users could result in poorer, rather than better, designed buildings. The thermal-probe technique for the measurement of the thermal conductivities of building structural materials has been assessed. This rapid transient and potentially cheap technique could be suited ideally to measurements in such materials. The theoretical basis for the method has been investigated and the accuracies and repeatabilities of thermal-probe instruments have been determined in measurements with paraffin wax. Determinations made with this technique, for masonry and structural components, were found to agree well with the manufacturer's thermal conductivity data. However, further developments need to be made to improve the usefulness of this technique for measuring the effective conductivities of fibrous insulants. Also the thermal-probe technique has been assessed for use in moist materials. Initial investigations with wet-day specimens showed that the probe diameter had no significant effect on the indicated values of the apparent thermal conductivity. Tests to measure the apparent thermal conductivities of aerated concrete blocks, at various moisture contents, gave results that compared well with other published data. Attempts to reduce national energy demands have led to increases in insulation thicknesses in roof spaces in Northern Europe and North America. It has generally been assumed that the apparent thermal conductivity of each material used has been a constant and equal to the value obtained in the testing laboratory. Examination of the temperature profiles through various horizontal thicknesses of loose-fill mineral wool insulants suggests that radiation effects and convection in the upper surface layers exposed to free air result in much larger apparent thermal conductivity values than those generally quoted in the literature, and the magnitudes of these effects also increase with the thickness of the insulant layer. Heat transfer mechanisms have been examined to explain these phenomena. Mathematical models of heat transfers through multi-phase materials have been examined. A model is proposed to describe the thermal conductivity of high-porosity cellular insulant which includes heat transfers by conduction through the solid and gaseous phases and by radiation. Predictions were found to agree well with experimental data for airfilled polystyrene foams and to be of the correct order of magnitude for air/fluorocarbon filled polyurethane foams.